Field identification of drought tolerant wheat genotypes using canopy vegetation indices instead of plant physiological and biochemical traits - Pengfei Wen; Yu Meng; Chenkai Gao; Xiaokang Guan; TongChao Wang; Wei Feng (Ecological Indicators, 2023)
Seasonal drought is a major limiting factor for wheat production in the North China Plain. The use of non-destructive screening tools based on vegetation indices associated with physiological and biochemical traits will help in the identification of drought-tolerant wheat genotypes to counter drought stress. The objectives of this study were to characterize the performance of 10 wheat genotypes with different genetic backgrounds in terms of physical and biochemical traits under two contrasting moisture regimes, and to evaluate the effectiveness of vegetation indices/spectral measurement techniques for assessing drought tolerance in wheat. Traits associated with drought stress were assessed in the 10 wheat genotypes, including plant biophysical parameters, drought tolerance parameters, as well as various vegetation indices. Significant variability was found wheat genotypes with different genetic backgrounds to water stress. The clustering results indicated that Luohan-19, Luohan-22, and Jinmai-47 were drought-tolerant genotypes characterized by high stress tolerance index (STI) values (0.548, 0.535 and 0.523, respectively), drought index (DI) values (0.517, 0.524 and 0.504, respectively), and drought tolerance coefficient (DC) values (1.065, 1.074 and 1.000, respectively). Based on principal component analysis and membership function, genotypes were classified as tolerant (Luohan-19, Luohan-22, and Jinmai-47), moderately tolerant (Luomai-26, Zhongmai-175, and Bainong-207) and sensitive (Yunong-516, Zhongmai-895, Annong-0711 and Huacheng-3366) to water stress, with comprehensive evaluation values (D) of >0.761, 0.422–0.761, and <0.422, respectively. Heatmap analysis of various vegetation indices for screening wheat genotypes showed similar results to the multivariate data analysis; that is, genotypes Luohan-19, Luohan-22, and Jinmai-47 were identified as drought-tolerant genotypes. Among these vegetation indices, the normalized difference water index (NDWI) and the red edge chlorophyll index (CIred edge) were highly correlated with the drought tolerance indices, such as STI and DI (r2 >0.717), and are therefore recommended as rapid indicators for the identification of tolerance genotypes in the field. These vegetation indices, particularly NDWI and CIred edge, exhibited similar performance to the drought tolerance indices and multivariate data analysis results in identifying drought-tolerant genotypes, and thus they can be used as alternative and inexpensive measures for identifying drought tolerance in wheat in the future.